A rapid and simple liquid chromatography‐tandem mass spectrometry method for the measurement of testosterone, androstenedione, and dehydroepiandrosterone in human serum. Issue 5 (2nd December 2016) - Xu, Wenjuan; Li, Huijun; Guan, Qing; Shen, Ying; Cheng, Liming
Abstract : Background: The assay of androgens plays an important role for the differential diagnosis of androgen‐related endocrine diseases. We developed a rapid and simple liquid chromatography tandem mass spectrometry (LC‐MS/MS) method with small sample volume and simple sample preparation for simultaneous determination of serum testosterone, androstenedione and dehydroepiandrosterone (DHEA) in adults. Methods: We spiked 100 μL of serum with 200 μL of internal standard solution, which was prepared in methanol, for matrix effect relief and protein precipitation. The obtained supernatant was used directly for LC‐MS/MS analysis. Results: The validated method exhibits excellent linearity for each analyte with linear correlation coefficient above 0.992. The total precisions at three concentrations were 15.66%, 8.81% and 4.34% for testosterone, 13.60%, 6.62% and 5.96% for androstenedione, 14.35%, 15.34% and 13.92% for DHEA, respectively. Recovery, carryover, matrix effect and analytical specificity were also performed for well validation of this LC‐MS/MS method with satisfied results. Reference intervals (5th‐95th centile) were also established for adult men and women. Discussion: This method offers simpler implement for quantification of steroids in clinical laboratories with minimal manual sample manipulation and minimized sample volume requirements. Conclusion: It is demonstrated that a reliable, simple, sensitive and potential method for steroids assay in clinical laboratories had been successfully developed by LC‐MS/MS.